STUDI ELEKTROKIMIA POLIANILIN KOMPOSIT ELEKTRODA PASTA KARBON - , Suriyanti (Jurnal Biofisika, 2013)
Polyaniline is widely used as a material for manufacturing electrodes such as biosensor, biofuel cell, and supercapacitor application in nanocomposite forms. In this study, polyaniline has been synthesized in emeraldyne salt forms by interfacial polymerization method and synthesized nanocomposite electrode of polyanilinecarbon paste. The polyaniline morphology was characterized by X - Ray Diffraction (XRD ) , Scanning Electron Microscopy ( SEM ), Transmission Electron Microscope (TEM) and Fourier Transform Infrared (FTIR). In XRD pattern showed crystal type was polyaniline nanofiber semicrystalline. The SEM image showed polyaniline morphology which nanoparticle formed. The TEM result estabilished nano-size indicated by diameter size about 60 -80 nm, FTIR result showed that polyaniline which synthesized was conductive polyaniline forms or called emeraldine salt (ES). Electrochemical studies showed that nanocomposite electrode of polyaniline-carbon paste be able to increased the ion transfer efficiency in the composite electrode. Voltammograms of nanocomposite electrode of polyaniline-carbon paste seen at a potential 0,5V aniline oxidation peaks and reduction peaks seen at -0.1 V Both of these curves peaks (oxidation and reduction was not observed clearly).